Metode Mendongeng Kreatif dalam Meningkatkan Literasi Baca Tulis Anak Usia Dini - Dina, Dina; Jamila, Jamila; Juariyah, Juariyah; Yulianti, Silvia; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study focuses on how storytelling activities presented in a variety of ways, such as using voice intonation, visual media, puppets, gestures, and improvised storylines, can create a more interactive and meaningful learning experience for children. This method is considered a more flexible alternative for literacy learning compared to conventional methods, which are usually one-way and uninteresting for children. The results of the study showed that creative storytelling increases children's vocabulary, improves their phonological awareness, enhances their ability to understand the storyline, and increases their interest in reading and writing activities. The livelier storytelling can also help create a comfortable learning environment and encourage children to actively participate. Overall, this study shows that creative storytelling is an effective and useful method for helping young children learn to read and write well.